2007
DOI: 10.1002/cmdc.200700070
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Protease Inhibitors as Antiplasmodial Agents. Part I: Aziridines and Epoxides

Abstract: A broad protease-based and cell-based screening of protease inhibitors yielded the aziridine-2-carboxylic acid derivative 2 a and the N-acylated aziridine-2,3-dicarboxylic acid derivatives 32 a and 34 b as the most potent inhibitors of falcipain-2 and falcipain-3 (IC(50) falcipain-2: 0.079-5.4 microM, falcipain-3: 0.25-39.8 microM). As the compounds also display in vitro activity against the P. falciparum parasite in the submicromolar and low micromolar range, these compound classes are leads for new antiplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 36 publications
0
43
0
2
Order By: Relevance
“…Peptidyl vinyl sulfones like K11777 were developed in a medicinal chemistry program to inhibit human cathepsins in vivo, including cathepsins B, L, and S, but not cathepsin C (49,50). Also, K11777 is known to target cysteine proteases in a number of parasitic organisms, including "cruzain," the cathepsin L-like protease target in T. cruzi (33,51), and the falcipains of P. falciparum (52). Accordingly, we hypothesized that the cathepsin L-like cryptopain 1 and/or 2 is likely an in vivo target for K11777.…”
Section: K11777 Eliminates C Parvum Infection From Cell Lines In Vitromentioning
confidence: 99%
“…Peptidyl vinyl sulfones like K11777 were developed in a medicinal chemistry program to inhibit human cathepsins in vivo, including cathepsins B, L, and S, but not cathepsin C (49,50). Also, K11777 is known to target cysteine proteases in a number of parasitic organisms, including "cruzain," the cathepsin L-like protease target in T. cruzi (33,51), and the falcipains of P. falciparum (52). Accordingly, we hypothesized that the cathepsin L-like cryptopain 1 and/or 2 is likely an in vivo target for K11777.…”
Section: K11777 Eliminates C Parvum Infection From Cell Lines In Vitromentioning
confidence: 99%
“…Derivatives containing aziridine-2-carboxylic acid and aziridine-2,3-dicarboxylic acid as electrophilic building blocks were synthesized to develop new selective inhibitors (25,26). In further investigations, aziridine-based inhibitors containing aziridine-2,3-dicarboxylates [Azi(OBn) 2 s] showed selective inhibition of cathepsin L-like enzymes, for instance, rhodesain, the major trypanosomal papain-like CP of the parasite Trypanosoma brucei rhodesiense (41), and falcipain-2 and falcipain-3 from the malaria parasite Plasmodium falciparum (29). In addition, aziridine-2,3-dicarboxylate-based inhibitors had antiparasitic activity against Trypanosoma brucei brucei and P. falciparum in vitro (29,41).…”
mentioning
confidence: 99%
“…In further investigations, aziridine-based inhibitors containing aziridine-2,3-dicarboxylates [Azi(OBn) 2 s] showed selective inhibition of cathepsin L-like enzymes, for instance, rhodesain, the major trypanosomal papain-like CP of the parasite Trypanosoma brucei rhodesiense (41), and falcipain-2 and falcipain-3 from the malaria parasite Plasmodium falciparum (29). In addition, aziridine-2,3-dicarboxylate-based inhibitors had antiparasitic activity against Trypanosoma brucei brucei and P. falciparum in vitro (29,41). Finally, this promising series of peptidomimetic aziridine-2,3-dicarboxylate inhibitors was demonstrated to exert significant antileishmanial activity.…”
mentioning
confidence: 99%
“…Therefore, the identification and synthesis of highly selective protease inhibitors might be a promising means for the treatment of such infections in future. In recent years, we have been working on the development of inhibitors of papain-like CPs belonging to the CAC1 family (13)(14)(15)(16)(17)(18). These proteases may represent attractive targets because of their key roles in parasite infections (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…In previous studies, we identified two peptidomimetic aziridine-2,3-dicarboxylate-based inhibitors, Boc-(S)-Leu-(R)-Pro-(S,S)-Azi-(OBn) 2 (compound 13b) and Boc-(R)-Leu-(S)-Pro-(S,S)-Azi-(OBn) 2 (compound 13e), exerting excellent antileishmanial activities, in a series of inhibitors of CL and CL-like CPs (15,16,26,27). Both aziridines targeted the leishmanial CB-like enzyme LmaCatB (L. major CPC), as documented with a biotin-tagged derivative of 13b (27).…”
mentioning
confidence: 99%